Expression of Relaxin 3 in the Ovarian Follicle of Japanese Quail - Khoi X. Hoang; Mei Matsuzaki; Tetsuya Kohsaka; Tomohiro Sasanami (The Journal of Poultry Science, 2023)
The relaxin (RLN) gene is expressed in the reproductive tracts, such as the ovary and uterus, of mammalian species. Although RLN expression is detected in the chicken ovary, detailed clarification of the physiological role of RLN has not yet been reported. To address this issue, in the present study we aimed to examine the spatiotemporal expression and hormonal control of RLN in Japanese quail. By performing semi-quantitative and quantitative reverse transcription-polymerase chain reaction analysis, we found that RLN mRNA was mainly expressed in the granulosa and theca layers of the ovary. The expression level in the granulosa layer increased with the stage of follicular development. Results from granulosa layer culture experiments revealed that RLN mRNA expression increased with the addition of estradiol-17β, whereas the addition of progesterone suppressed RLN transcription. More detailed analysis indicated that RLN expression was highest in the stigma region of the follicle but significantly decreased as the time of the expected luteinizing hormone (LH) surge approached. Together, our findings demonstrated that the granulosa cells in the mature preovulatory follicles constitute the main source of RLN in the Japanese quail. Because RLN expression was highest in the stigma region and the expression dramatically decreased following the LH surge, the results further suggest that RLN may be related to tissue remodeling for the ovulation process in birds.